ON THE QUESTION OF NEUTRINO SPIN PRECESSION IN A MAGNETIC-FIELD - Guzzo, M. M.; Bellandi, J. (Elsevier B.V., 1992)
Using the Feynman procedure of ordered exponential operators we solve the evolution equations for a two-neutrino system considering arbitrarily varying matter density and magnetic field along the neutrino trajectory. We show that a large geometrical phase velocity suppresses nu(L) --> nu(R) transitions unless some stationary trajectory is found along the neutrino path. Concerning the solar neutrino case, if we admit the standard solar model matter distribution, no such trajectory can be found.